2012
DOI: 10.1007/s11033-012-1581-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of single-nucleotide polymorphisms at the TP53-binding and responsive promoter region of BCL2 gene in modulating the phenotypic variability of LGMD2C patients

Abstract: Apoptosis of skeletal muscle fibers is a well-known event occurring in patients suffering from muscular dystrophies. In this study, we hypothesized that functional polymorphisms in genes involved in the mitochondrial apoptotic pathway might modulate the apoptotic capacity underlying the muscle loss and contributing to intrafamilial and interfamilial variable phenotypes in LGMD2C (Limb Girdle Muscular Dystrophy type 2C) patients sharing the same c.521delT mutation in SGCG gene. Detection of apoptosis was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Severe or prolonged stress leads to apoptosis via p53 activation of BAX5 and PUMA [71] as well as by repression of anti-apoptotic [72] and cell cycle [73] genes. Recently there have been reports of p53 upregulation in muscle being linked to muscle atrophy in Huntington’s disease [74] and LGMD2C [75]. Another case of p53 being associated with muscle weakness is ageing, in which there is a notable loss of muscle mass and an increase in adipose tissue resulting in a decline in skeletal muscle [76].…”
Section: Discussionmentioning
confidence: 99%
“…Severe or prolonged stress leads to apoptosis via p53 activation of BAX5 and PUMA [71] as well as by repression of anti-apoptotic [72] and cell cycle [73] genes. Recently there have been reports of p53 upregulation in muscle being linked to muscle atrophy in Huntington’s disease [74] and LGMD2C [75]. Another case of p53 being associated with muscle weakness is ageing, in which there is a notable loss of muscle mass and an increase in adipose tissue resulting in a decline in skeletal muscle [76].…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, in the mdx mouse model and in patients affected by Duchenne dystrophy, upregulation of pro-apoptotic proteins such as Bax and caspases were detected in myofibers, suggesting that under pathological conditions, these myofibers undergo apoptosis. 22-24 Apoptosis and decreased Bcl-2 expression were detected in other muscular dystrophies such as Limb Girdle MD type 2C, 25 and congenital MD type 1A. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The gene SGCG encodes gamma (γ)-sarcoglycan, one of several sarcolemmal transmembrane glycoproteins that interact with dystrophin (15). It was shown that the sarcoglycan null mice, which lacked the sarcoglycan complex in skeletal muscle and adipose tissue, were glucose-intolerant and exhibited whole body insulin due to impaired insulin-stimulated glucose uptake in skeletal muscles (16).…”
Section: Discussionmentioning
confidence: 99%